Chahī Mālekā Johrā : bibira chaoāla joāba - Bāhāuddina Ākhuñji (Brittle Bangla books., 1926)
Islamic instruction in the form of questions and answers between the Arakanese princess Johra Bibi and a Muslim fakir.